San Anton Printers, Inc. a production system study - Baking, Arnold; Castillo, Tatan; Raroque, Vic.; Reyes, Mandy (Diliman, Quezon City College of Engineering, 1990)
San Anton Printers, Inc. is a fami1y owned enterprise which caters to the printing needs of its clientele mainly composed of friends and relatives. It boasts of high quality printing services from stationeries, calling cards, wedding invitations,posters, letterheads, and book printing. Its technical capability range from letterpress printing to lithography. As a production system, it relies on an irregular demand with each job order being unique (has its own specifications) from the other. Basically,, the system is a job shop. Because of its small scale operation and the uncertainty of demand, it does not utilize any forecasting method and do not inventory. Production planing mainly consists of jobs sequencing and scheduling. It maintains a regular personnel compliment working on an eight-hour shift, with three printing machines. Excess capacity requirements are absorbed by overtime. After studying and scrutinizing their present set-up, the group came up with several recommendations; designate a specific storage area to decongest the already narrow passageways and to limit fire hazards to the storage area using CORELAP, the group has obtained an improved model and has transformed this to fit the existing physical layout. We reserved the central area only for printing activities, because of the simplicty of the printing process, the group decided not to revise the set of procedures followed by the firm, maintain complete records of sales and volume printed for each machines so that trends may be easily discerned ( a sample record sheet will be shown), the group has shown that the sales is not seasonal so the firm may use yearly forecasts and break it down to monthly estimates, the group agrees with the company's policy of not having an inventory of ink, paper, and chemicals because of the nature of a printing press, proper records of excess raw materials including job for which the paper was used, type of paper and date purchased, breakdown a job into its basic operations, classify a job order into the operations involved set up standard times based on the operation and not on the job, keep complete records of production as to type of jobs processed, quantity, actual processing time per job and overtimes, set up standard processing times, install exhaust fans, additional lighting, and noise absorbers, used a dispenser for cards to prevent toppling of stacked cards, place adhesives on one finger to facilitate picking up of paper, change the hand-controlled pause lever to one that is foot-controlled, standardize composition position inside the rama for common printing jobs requiring the same dimensions such as calling cards. Regular inspections of the machines alonng with fumigation and general house cleaning activities should be scheduled at least once a month.
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems.
Keywords: San Anton Printers Incorporated; Printing industry; Production engineering